Practising family law - Serisier, Ian David; Altobelli, Tomm (Chatswood, NSW : LexisNexis Butterworths, 2012)
The successful practice of family law requires mastery of a complex combination of skills and knowledge. This book takes up where theory leaves off, providing clear practical guidance on how to conduct family law matters.
Includes cases and statutes.
Previously published: 2009.
Includes bibliographical references and index.
Keywords: Family law -- Australia; Family law -- Australia -- Cases; Domestic relations courts -- Australia; Australian